215 Preventing heat stress before the Tokyo olympic games, the case of open water. (3rd March 2020) - Pla, Robin; Aubry, Anaël
Abstract : Background: A huge heat stress is expected during the Tokyo 2020 Olympic Games, especially for the open-water swimming event. Literature is scarce about the physiological responses to open-water swimming events in warm water. Objective: The purpose of this study was to collect data from Tokyo's thermal environment one year before the Olympic Games and to observe the physiological responses of swimmers participating in the test event. Design: Individual deep body temperatures were collected before, during and after an open-water 5-km race. Thermal environment was also collected. After the race, a simple questionnaire was administrated to the swimmers, to evaluate their perceived heat stress. Setting: The study took place during the open-water swimming Olympic test event in Tokyo. Patients (or Participants): Three world-class open-water swimmers (two males and two females) participated in the study. All were selected by the french swimming federation. Interventions (or assessment of risk factors): Some pre-cooling strategies were used before the race as wearing cooling jacket, drinking cold beverages, putting a wet towel on the neck. Main outcome measurements: The main outcome of the study was to report the individual temperature regulation in order to prevent hyperthermia syndrome for the next Summer Olympic Games. Results: At the end of the race (8:00 AM), the water temperature was 30.3°C and the relative humidity was 61.1%. Individual body temperatures were 39.2°C, 39.5°C and 39.7°C whereas the average body temperature at the beginning of the race was 37.2°C. The survey findings indicate that swimmers perceived a high to very high heat stress during the race. Conclusions: The Olympic organizing committee should consider these results to better avoid hyperthermia on open-water swimmers, in determining the timings on the events. The swimmers and background staffs need to use appropriate heat acclimatization strategies to reduce the risk of heat illness and to maximize swimming performance.